1997
DOI: 10.1046/j.1365-2141.1997.2393053.x
|View full text |Cite
|
Sign up to set email alerts
|

Crossover study of the haematological effects and pharmacokinetics of glycosylated and non‐glycosylated G‐CSF in healthy volunteers

Abstract: Summary.A cross-over study of glycosylated and nonglycosylated G-CSF was performed in 20 healthy male volunteers to compare the effects of the different forms of G-CSF, the extent of inter-individual progenitor cell mobilization and to determine whether any differences observed were related to the serum concentrations of G-CSF attained. The peak WBC achieved during 6 d of G-CSF administration at a dose of 5 mg/kg/d was significantly higher with the glycosylated than the non-glycosylated product (P ¼ 0 . 02) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
5
63
2
Order By: Relevance
“…In a group of healthy volunteers, Høglund et al 27 found lenograstim to be 25% superior to filgrastim in terms of CD34 + cell and CFU-GM mobilization. The same study design was used by Watts et al 28 However, in their study there was no difference in CD34 + cell mobilisation, but the number of GM-CFC was higher in the lenograstim-treated subjects. Watts et al 28 also compared day-1 G-CSF plasma levels and found filgrastim levels to be significantly higher than lenograstim levels.…”
Section: Who Demonstrated That Dailymentioning
confidence: 92%
See 3 more Smart Citations
“…In a group of healthy volunteers, Høglund et al 27 found lenograstim to be 25% superior to filgrastim in terms of CD34 + cell and CFU-GM mobilization. The same study design was used by Watts et al 28 However, in their study there was no difference in CD34 + cell mobilisation, but the number of GM-CFC was higher in the lenograstim-treated subjects. Watts et al 28 also compared day-1 G-CSF plasma levels and found filgrastim levels to be significantly higher than lenograstim levels.…”
Section: Who Demonstrated That Dailymentioning
confidence: 92%
“…19,35 However, while the effect of the presence of neutrophils increases daily, the pharmacokinetic studies were only done on day 1 of G-CSF treatment. 28 If glycosylated rhG-CSF was neutralised less effectively by neutrophils, this could explain better CD34 + or GM-CFC harvest and higher maximum WBC in probationers with very high neutrophil counts. 25,27,28 During neutropenia, this difference would not come into play, which might explain why, even if there were a difference between the two G-CSF preparations in terms of receptor binding, in neutroBone Marrow Transplantation penic hosts consistently no difference was found between glycosylated and non-glycosylated G-CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, randomised clinical trials with an original (cross-over) design have been reported. 4,5 High-dose chemotherapy followed by autologous PBPC transplantation was a widely used procedure to treat metastatic and high-risk breast cancer patients. Since reported randomised clinical trials were negative and fraudulent studies were audited, 6 this indication is decreasing.…”
mentioning
confidence: 99%